Answer:
The answer is option A
Explanation:
f(x) = (x+1)³ + 4
To find f-¹(x) equate f(x) to y
That's
y = (x+1)³ + 4
Next interchange the terms x becomes y and y becomes x
That's
x = ( y+1)³ + 4
Make y the subject
(y+1)³ = x - 4
Find the cube root of both sides
That's
![y + 1 = \sqrt[3]{x - 4}](https://img.qammunity.org/2021/formulas/mathematics/college/bcbd7kz7c2hor2q78hv6i3qazikml5zy8u.png)
Send 1 to the right side of the equation
That's
![y = \sqrt[3]{x - 4} - 1](https://img.qammunity.org/2021/formulas/mathematics/college/i2fxp16fbne3v9k5agp2om4ngx6r0iyxow.png)
So we have the final answer as
![f ^( - 1) (x) = \sqrt[3]{x - 4} - 1](https://img.qammunity.org/2021/formulas/mathematics/college/654ksgs7qyyi0fzyjigo3vr1yu1ep4roex.png)
Hope this helps you